Telemedicine in Community Cancer Care: How Technology Helps Patients With Cancer Navigate a Pandemic. Issue 1 (12th January 2021) - Patt, Debra A.; Wilfong, Lalan; Toth, Sara; Broussard, Stephanie; Kanipe, Kristen; Hammonds, Jason; Allen, Victoria; Mautner, Beatrice; Campbell, Nakedra; Dubey, Ajay K.; Wu, Nini; Neubauer, Marcus; et al.
Abstract : COVID-19 places unprecedented demands on the oncology ecosystem. The extensive pressure of managing health care during the pandemic establishes the need for rapid implementation of telemedicine. Across our large statewide practice of 640 practitioners at 221 sites of service, an aggressive multidisciplinary telemedicine strategy was implemented in March by coordinating and training many different parts of our healthcare delivery system. From March to September, telemedicine grew to serve 15%-20% of new patients and 20%-25% of established patients, permitting the practice to implement safety protocols and reduce volumes in clinic while continuing to manage the acute and chronic care needs of our patient population. We surveyed practice leaders, queried for qualitative feedback, and established 76% were satisfied with the platform. The common challenges for patients were the first-time use and technology function, and patients were, in general, grateful and happy to have the option to visit their clinicians on a telemedicine platform. In addition to conducting new and established visits remotely, telemedicine allows risk assessments, avoidance of hospitalization, family education, psychosocial care, and improved pharmacy support. The implementation has limitations including technical complexity; increased burden on patients and staff; and broadband access, particularly in rural communities. For telemedicine to improve as a solution to enhance the longitudinal care of patients with cancer, payment coverage policies need to continue after the pandemic, technologic adoption needs to be easy for patients, and broadband access in rural areas needs to be a policy priority. Further research to optimize the patient and clinician experience is required to continue to make progress.